HARMONISASI PROGRAM RUANG PANTI WREDA: STRATEGI DALAM MENINGKATKAN KESEJAHTERAAN LANSIA - Buntarman, Caren; Hadiwono, Alvin (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
The global phenomenon of an increasing elderly population has given rise to issues regarding the lack of facilities that comprehensively accommodate the physical and psychological needs of the elderly. In Indonesia, the primary problem is the limited availability of nursing homes (panti wreda) that offer optimal services for elderly well-being, particularly in terms of mental health, which is often neglected. The objective of this design project is to create a regenerative architecture-based nursing home with a well-being approach to holistically improve the quality of life for the elderly. The method employed is a symbiotic approach combined with holistic architectural design, focusing on creating mutually beneficial relationships between humans, space, and the environment by integrating natural elements that support ecosystem balance and elderly well-being. The design steps include selecting a site in Cadas Ngampar that supports tranquility and accessibility, developing a spatial program based on elderly needs, and integrating the concept of therapeutic gardening through regenerative hydroponics as a meaningful activity. The result is a nursing home design that provides housing tailored to elderly conditions, spaces for physical and psychological therapy, an educational sensory gallery, and herbal hydroponic gardening areas. The findings indicate that spaces designed with a regenerative approach can effectively address mental health issues and enhance elderly social interaction. The spatial novelty lies in the integration of healing functions, public education, and elderly engagement in regenerative activities, which also strengthen intergenerational relationships and raise awareness about life in old age. Keywords:  harmony, hydroponics, regenerative, senior care home, well-being Abstrak Fenomena meningkatnya populasi lansia secara global melahirkan isu tentang kurangnya fasilitas yang mampu mengakomodasi kebutuhan lansia secara fisik dan psikologis secara menyeluruh. Masalah yang muncul di Indonesia adalah minimnya panti wreda yang memberikan pelayanan optimal terhadap kesejahteraan lansia, terutama dalam aspek kesehatan mental yang kerap terabaikan. Tujuan dari perancangan ini adalah menciptakan panti wreda berbasis arsitektur regeneratif dengan pendekatan well-being untuk meningkatkan kualitas hidup lansia secara holistik. Metode yang digunakan adalah simbiosis dengan pendekatan perancangan arsitektur holistik yang diterapkan untuk menciptakan program ruang yang mampu merespons kebutuhan landia secara melalui hubungan yang harmonis dan simbiosis. Langkah perancangan meliputi pemilihan tapak di Cadas Ngampar yang mendukung ketenangan dan aksesibilitas, perumusan program ruang berdasarkan kebutuhan lansia, serta integrasi konsep therapeutic gardening dengan hidroponik regeneratif sebagai aktivitas bermakna. Hasil dari perancangan ini adalah rancangan panti wreda yang menyediakan hunian sesuai kondisi lansia, ruang terapi fisik dan psikologis, galeri sensori edukatif, serta area berkebun hidroponik herbal. Temuan dari penelitian ini menunjukkan bahwa ruang yang dirancang dengan pendekatan regeneratif mampu menangani permasalahan kesehatan mental dan meningkatkan interaksi sosial lansia. Kebaruan dari keruangan yang diangkat terletak pada integrasi antara fungsi penyembuhan, edukasi publik, dan keterlibatan lansia dalam aktivitas regeneratif yang juga memperkuat hubungan antargenerasi dan kesadaran akan kehidupan di masa tua.